Public expenditure inflation and growth: a macro-econometric analysis for India - "Bhattacharya , B . B." (Delhi, 1984)
The trade-off between inflation and growth is a major issue in economics, and in developing countries the problem arises mainly as a result of the dual roles played by public expenditure--which generates income and employment--and deficit financing--which triggers inflation. In this empirical analysis of the issues involved, the author uses a disaggregated macro-economic model specially developed for the mixed economy of India to discuss government budgetary constraints, resource mobilization, money supply and price levels, investment and growth, and price-wage spirals in the Indian economy.
Keywords: Macroeconomic